WHAT’S GOING ON? DIVERSITY, EQUITY, AND INCLUSION DISPUTE RESOLUTION INITIATIVES IN THE U.S. - Robyn Weinstein (Washington University Journal of Law and Policy, 2024)
I was motivated to write this article for two reasons; first, to create a comprehensive resource for those seeking to create or build diversity, equity and inclusion dispute resolution initiatives in their local communities, and second, to share some thoughts about how we (members of the dispute resolution field) might continue to work collectively to increase diversity, equity and inclusion.
Keywords: Diversity; Equity; Inclusion; Dispute; Resolution